Menumbuh kembangkan Berpikir Logis dan Sikap Positif terhadap Matematika melalui Pendekatan Matematika Realistik - Subekti, Evina Eka (MALIH PEDDAS, 2011)
Abstrak: Â The process of learning mathematics that implemented in the classroom become very interesting issue for discussion. This is because meaningful learning is expected to enhance students logical thinking abilities and positive attitudes towards mathematics still very rare. There was only the memorization process of mathematical concepts that are mechanistical. As a result, some research indicates that student learningâs result is not satisfactory. This paper describes the mathematical approach theoretically realistic to develop logical thinking ability and positive attitude of students towards mathematics that can ultimately improve student learningâs result. Â Key words: logical thinking, positive attitude, realistic mathematic